Odpowiedź :
Odpowiedź:
[tex]a)1 - \frac{4}{7} = \frac{7}{7} - \frac{4}{7} = \frac{3}{7} \\ b)1 - \frac{2}{5} = \frac{5}{5} - \frac{2}{5} = \frac{3}{5} \\ c)2 - \frac{5}{8} = \frac{16}{8} - \frac{5}{8} = \frac{11}{8} = 1 \frac{3}{8} \\ d)6 - \frac{3}{4} = \frac{24}{4} - \frac{3}{4} = \frac{21}{4} = 5 \frac{1}{4} \\ e)8 - 1 \frac{6}{7} = \frac{56}{7} - \frac{13}{7} = \frac{43}{7} = 6 \frac{1}{7} \\ f)12 - 5 \frac{7}{13} = \frac{156}{13} - \frac{72}{13} = \frac{84}{13} = 6 \frac{6}{13} \\ g)5 - 2 \frac{3}{5} = \frac{25}{5} - \frac{13}{5} = \frac{12}{5} = 2 \frac{2}{5} \\ h)9 - 5 \frac{4}{7} = \frac{63}{7} - \frac{39}{7} = \frac{24}{7} = 3 \frac{3}{7} [/tex]
liczę na naj